Imaging mGluR5 Dynamics in Astrocytes Using Quantum Dots. Issue 1 (16th February 2018) - Arizono, Misa; Bannai, Hiroko; Mikoshiba, Katsuhiko
Abstract: This unit describes the method that we have developed to clarify endogenous mGluR5 (etabotropic tamate eceptors 5) dynamics in astrocytes by single‐particle tracking using quantum dots (QD‐SPT). QD‐SPT has been a powerful tool to examine the contribution of neurotransmitter receptor dynamics to synaptic plasticity. Neurotransmitter receptors are also expressed in astrocytes, the most abundant form of glial cell in the brain. mGluR5s, which evoke intracellular Ca 2+ signals upon receiving glutamate, contribute to the modulation of synaptic transmission efficacy and local blood flow by astrocytes. QD‐SPT has previously revealed that the regulation of the lateral diffusion of mGluR5 on the plasma membrane is important for local Ca 2+ signaling in astrocytes. Determining how mGluR5 dynamics are regulated in response to neuronal input would enable a better understanding of neuron‐astrocyte communication in future studies. Curr. Protoc. Neurosci . 66:2.21.1‐2.21.18. © 2014 by John Wiley & Sons, Inc.